TINDAK PIDANA KEJAHATAN KORPORASI DALAM KASUS KORUPSI TIMAH DI BANGKA BELITUNG - Fadly, Ovan Setyawan; Multiwijaya, Vience Ratna; Suar, Aprima (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
In the year 2024, a case of tin corruption in Bangka Belitung was uncovered, resulting in a state loss of approximately IDR 300 trillion. Investigators have identified 22 suspects. Perpetrators not only include individuals but also involve corporations (legal entities). Therefore, criminal penalties should also be imposed on corporate entities. This study aims to formulate the application of criminal sanctions for corporate crime in the tin corruption case in Bangka Belitung. The research methodology employs a normative juridical approach using secondary data through literature review by examining primary, secondary, and tertiary legal materials. In this case, the Prosecutor applies Article 2 Paragraph (1) and Article 3 jo. Article 18 of Law No. 31 of 1999 jo. Article 55 Paragraph (1) of the Criminal Code and Article 3 and 4 of Law No. 8 of 2010 jo. Article 55 Paragraph (1) of the Criminal Code. In this case, the Prosecutor does not implement the Article 6, Article 7, Article 9, and Article 20 Paragraphs (1), (2), (7) of Law No. 8 of 2010 and Article 87, Article 90 Paragraph (1), Article 91 Paragraph (1), Article 116, Article 117, Article 118, Article 119, and Article 120 of Law No. 32 of 2009, which are related to Corporate Criminal Offenses.Keywords: Corruption, Tin, Corporation, Criminal Act, Crime